2022
DOI: 10.1128/jvi.00704-22
|View full text |Cite
|
Sign up to set email alerts
|

The Dengue Virus Nonstructural Protein 1 (NS1) Interacts with the Putative Epigenetic Regulator DIDO1 to Promote Flavivirus Replication in Mosquito Cells

Abstract: Dengue is the most important mosquito-borne viral disease to humans. Dengue virus NS1 is a multifunctional protein essential for replication and modulation of innate immunity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 67 publications
0
4
0
Order By: Relevance
“…Amongst the cellular interactors enriched in NS5 immunoprecipitations, we identified three elements of the survival of motor neuron (SMN) complex involved in the spliceosome and small nuclear ribonucleoprotein (snRNP) assembly (Gemini 2, Gemini 3 and Smn) as well as the E3 ligase HYD (ortholog of human UBR5). In mammals, the OST complex and proteasome have previously been described as proviral host factors interacting with DENV NS1 [ 10 , 31 33 ], NS5 was shown to hijack the snRNP and UBR5 was purified with NS5 [ 13 ], illustrating virus-host interactions that occur both in the mosquito vector and human host. Together, these data validate our experimental model to identify physiologically relevant protein-protein interactions between virus and mosquito vector.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Amongst the cellular interactors enriched in NS5 immunoprecipitations, we identified three elements of the survival of motor neuron (SMN) complex involved in the spliceosome and small nuclear ribonucleoprotein (snRNP) assembly (Gemini 2, Gemini 3 and Smn) as well as the E3 ligase HYD (ortholog of human UBR5). In mammals, the OST complex and proteasome have previously been described as proviral host factors interacting with DENV NS1 [ 10 , 31 33 ], NS5 was shown to hijack the snRNP and UBR5 was purified with NS5 [ 13 ], illustrating virus-host interactions that occur both in the mosquito vector and human host. Together, these data validate our experimental model to identify physiologically relevant protein-protein interactions between virus and mosquito vector.…”
Section: Resultsmentioning
confidence: 99%
“…We identified Loqs as an interactor of NS1, expressed as part of a polyprotein with other non-structural proteins flanked by non-viral UTRs, suggesting that Loqs was recruited to NS1 via protein-protein interactions. In contrast, Loqs was not identified in the interactome of NS1 expressed individually in mosquito cells [ 33 ]. Given that NS1 is an ER resident protein secreted through the secretory pathway [ 49 , 50 ] and that Loqs is a cytoplasmic protein, the interaction of Loqs with NS1 is likely to be an indirect one, mediated by other viral non-structural proteins interacting with NS1.…”
Section: Discussionmentioning
confidence: 99%
“…Their localization helps to enhance DENV replication [ 29 , 30 ]. C DENV NS1 interacts with DIDO1, a master epigenetic regulator and somehow elevates DENV replication [ 35 ]. D Capsid protein interacts with core histones (H2A, H2B, H3, and H4) and localizes them in cytoplasm to participate in DENV replication and propagation [ 36 ] …”
Section: Denv and The Host Epigenetic Machinerymentioning
confidence: 99%
“…Localization studies have shown that NS1 binds with the epigenetic regulator DIDO1 (Death Inducer Obligator 1) to promote virus replication, as shown in Fig. 3 C. The silencing of DIDO1 results in reduced virus replication, indicating its significant role [ 35 ]. The dengue structural protein capsid is found to localize in the nucleus and target the four core histones, H2A, H2B, H3, and H4.…”
Section: Denv and The Host Epigenetic Machinerymentioning
confidence: 99%
See 1 more Smart Citation